Spatial R&D spillovers and economic growth: Evidence from West Germany - Michael Funke; Annekatrin Niebuhr (Hamburg Institute of International Economics (HWWA), 2000)
The paper bases itself on recent theoretical writings in growth economics that empha-size the effects of both own R&D efforts and of interregional technology spillovers on regions productivity. We propose robust estimation techniques to evaluate the R&D spillovers across West German functional regions during the period 1976 - 1996. The findings suggest the existence of knowledge spillovers across functional regional boundaries. Moreover, significant spillovers are mainly found among geographically close regions. This finding confirms the hypothesis that proximity matters. – – Das Papier basiert auf jüngeren Beiträgen zur Wachstumstheorie, die den Stellenwert eigener F&E-Anstrengungen und interregionaler Spillover-Effekte für die regionale Produktivitätsentwicklung betonen. F&E-Spillover zwischen funktionalen Regionen in Westdeutschland werden auf der Grundlage robuster Regressionsmethoden für den Zeitraum zwischen 1976 und 1996 untersucht. Die empirischen Ergebnisse deuten darauf hin, dass Wissensspillover die Grenzen funktionaler Regionen überschreiten. Zudem sind signifikante Spillover-Effekte vor allem zwischen räumlich benachbarten Gebieten festzustellen. Dieses Resultat bestätigt die Hypothese, dass räumliche Nähe von wesentlicher Bedeutung ist.
Keywords: O57; F43; C52; C21; R11; 330; R&D Spillovers; Economic Growth; Germany; Forschung; Spillover-Effekt; Regionales Wachstum; Produktivität; Räumliche Interaktion; Schätzung; Deutschland; Alte Bundesländer